2020
DOI: 10.21203/rs.2.19960/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood amyloid β oligomerization as a biomarker of Alzheimer’s disease: a blinded validation study

Abstract: INTRODUCTION: Oligomeric amyloid ß (Aß) is one of the major contributors to the pathomechanism of AD; Aß oligomerization in plasma can be measured using a Multimer Detection System-Oligomeric Aß (MDS-OAß) after incubation with spiked synthetic Aß. METHODS: We evaluated the clinical sensitivity and specificity of the MDS-OAß values by inBlood TM OAß test using heparin-treated plasma samples from 52 AD patients in comparison with 52 community-based subjects with normal cognition (NC). The inclusion criterion wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A series of papers published recently by research consortium from Korea [75][76][77] represents the most advanced version of the prototype protocol for the detection of AβOs as a potential AD biomarker in blood using misfolded protein amplification techniques. To estimate AβO levels in blood plasma, soluble Aβ42 monomers were added ('spiked') into the aliquot of biological fluid, followed by the incubation of the mixture for 144 h. It has been shown that spiking of Aβ monomers to blood plasma samples led to an increase in AβO concentration, as measured by the increase of ThT fluorescence, when plasma sample originated from AD patient rather than normal control subject [76].…”
Section: Techniques Based On Amplification Of Misfolded Protein Conformationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of papers published recently by research consortium from Korea [75][76][77] represents the most advanced version of the prototype protocol for the detection of AβOs as a potential AD biomarker in blood using misfolded protein amplification techniques. To estimate AβO levels in blood plasma, soluble Aβ42 monomers were added ('spiked') into the aliquot of biological fluid, followed by the incubation of the mixture for 144 h. It has been shown that spiking of Aβ monomers to blood plasma samples led to an increase in AβO concentration, as measured by the increase of ThT fluorescence, when plasma sample originated from AD patient rather than normal control subject [76].…”
Section: Techniques Based On Amplification Of Misfolded Protein Conformationsmentioning
confidence: 99%
“…Recent work by Youn et al [77] reported further improvement of the AβO amplification technique. The analysis was conducted using commercially available kit (inBlood™ OAβ test), produced by People Bio Inc, Korea.…”
Section: Techniques Based On Amplification Of Misfolded Protein Conformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, 56% of these proteins were also increased in pregnant HF than SF ULF, and are involved in crucial biological events during the preimplantation period, such as energy metabolism (ACAA2, ENO1, MDH2, LOC615277, QPRT) [204,[495][496][497][498], glutathione synthesis (GSS) [499], attachment between trophectoderm and uterine LE (HSPA9) [500], de novo purine biosynthesis (ATIC) [501], amino acid metabolism (PSPH, GOT1, LAP3, WARS, AHCY) [502][503][504][505][506], and cytoskeletal organization and cell signaling (ACTN4, CAP1) [507,508].…”
Section: Discussionmentioning
confidence: 99%